86 Moving towards an enhanced community palliative support service (EnComPaSS): impact of using mobile technology to support delivery of community palliative care. Issue Volume 9: Issue (2019)Supplement 1 (March 2019) - Taylor, Paul; Mawson, Susan; Ariss, Steven
Abstract : Background: Models of community palliative care delivery are typically dependent on specialist nursing and medical staff acting independently. This study, part of the EnComPaSS project, appraises the impact of eShift, a technological system created by Sensory Technologies. eShift supports a delegated model of care, facilitating visiting staff to remain in ongoing contact with senior team members, and supporting systematic MDT recording. Methods: This was a service evaluation conducted at a Specialist Palliative Care service in the North of England, part of a real-world evaluation of a complex intervention. Prior data was collected from October 2014 to September 2015, transition to the new model began in October 2015, with data collection continuing to September 2016. Outcomes were based on prior hypotheses, including absolute numbers of patient contacts, grade of professional, number and route of hospital admissions and associated economic impact. Further evaluations over a longer time period are ongoing. Results: In comparing the pre-intervention period with the follow-up period, the total number of patients on the caseload remained relatively stable (1521 vs 1501). There was a reduction in total visits (3725 vs 3285), number of consultant visits (105 vs 48) and number of senior nurse visits (3361 vs 2730). There was an increase in the number of band 5 nurse (0 vs 208) and registrar visits (89 vs 170). Furthermore, number of patients admitted to hospital reduced (1238 vs 1156), as did overall admissions (5571 vs 4548) and average length of stay in days (6.23 vs 5.99). The reduction in hospital bed-days translates to a cost saving of £2.7 m per year, based on costs during the study period. Conclusion: This service evaluation supports the successful implementation of a technological solution to improving efficiency and delivery of community palliative care, with associated reductions in visits, hospital stays and service costs.